2016
DOI: 10.1016/j.jaci.2015.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment IgE sensitization patterns determine the molecular profile of the IgG4 response during updosing of subcutaneous immunotherapy with timothy grass pollen extract

Abstract: Pretreatment allergen component-specific IgE appears to determine the induction of IgG4 in the updosing phase. Induced IgG4 seems to suppress IgE levels on ISAC, resulting in a marked decrease in ISAC-measured specific IgE levels after updosing of SCIT. Thus this decrease in ISAC IgE levels can be used to monitor the blocking effect of allergen-specific immunotherapy-induced non-IgE antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 48 publications
(51 reference statements)
5
29
1
1
Order By: Relevance
“…One study demonstrated an association with clinical outcome parameters . Immuno‐solid‐phase allergy chip may also be applicable to monitor the induction of sIgG4 in the updosing phase of SCIT while it shows the application of ISAC in the updosing phase of AIT .…”
Section: Resultsmentioning
confidence: 99%
“…One study demonstrated an association with clinical outcome parameters . Immuno‐solid‐phase allergy chip may also be applicable to monitor the induction of sIgG4 in the updosing phase of SCIT while it shows the application of ISAC in the updosing phase of AIT .…”
Section: Resultsmentioning
confidence: 99%
“…The humoral response that marks allergen tolerance induction during AIT is characterized by a transient rise in allergen‐specific IgE followed by a decrease in IgE and a gradual increase in allergen‐specific IgG antibodies. IgG4 particularly increases during the course of AIT linked to continuous administration of the allergen, which results in a 10‐ to 100‐fold decreased ratio of allergen‐specific IgE:IgG4 . IgG4 production has been linked to Breg cells and they are considered as classical non‐inflammatory due to their specific structural and functional features: (i) they do not activate complement, (ii) they display low affinity for Fcγ receptors, and (iii) they are able to exchange Fab arms leading to unique functional bi‐specific monovalent antibodies .…”
Section: Allergen‐specific Immunotherapymentioning
confidence: 99%
“…IgG4 particularly increases during the course of AIT linked to continuous administration of the allergen, which results in a 10-to 100fold decreased ratio of allergen-specific IgE:IgG4. 183,188 IgG4 production has been linked to Breg cells 14 and they are considered as classical non-inflammatory due to their specific structural and functional features: (i) they do not activate complement, (ii) they display low affinity for Fcγ receptors, and (iii) they are able to exchange Fab arms leading to unique functional bi-specific monovalent antibodies. 189 Therefore, anti-inflammatory allergen-specific IgG4 may protect against allergic responses by competing with IgE for allergen binding.…”
Section: Immunologic Mechanisms Operating During Aitmentioning
confidence: 99%
“…Moreover, elevated IgE levels before treatment is thought to be a prerequisite for induction of IgG4 blocking antibodies. In addition IgE and IgG4 levels correlate with other functional immunological changes such as facilitated antigen binding, basophil sensitivity and clinical symptoms score [105]. …”
Section: Treatment Of Chronic Upper Airway Diseasementioning
confidence: 99%